Musculoskeletal syndrome treated with global postural re-education in double-redo lung transplantation: a case report with an 8-month follow-up - M. Polastri; G.M. Paganelli; G. Dolci; E. Di Ciaccio; I. Prediletto (PAGEPress Publications, 2022)
Postoperative pain and persisting fatigue represent critical concerns for patients receiving lung transplantation. The purpose of this study was to illustrate the trajectory of symptoms in a patient who presented with a posttransplant musculoskeletal syndrome after double redo-lung transplantation and attended therapeutic sessions of global postural re-education during the symptomatic phase. A 32-year-old woman with interstitial lung disease underwent double lung transplantation. At 23 months, functional parameters deteriorated, and the patient was placed on the active list for a second double-lung transplantation. Twenty months after re-transplantation, the patient reported continuous thoracic-lumbar musculoskeletal pain exacerbated by moving or performing the standard motor activities. Lower body flexibility improved during the observation period changed from -10 cm to 0 cm at the Chair Sitand- Reach Test. Leg strength improved as well, and the patient was able to perform more repetitions at the Squat Test, improving from 14 to 39. Pain intensity changed from 7 to 4 on a numerical rating scale. We observed that outcomes strictly related to treatment, with lower body flexibility, pain intensity, and physical function improving over time. As a result global postural re-education proved to be effective in this patient.